Health Literacy and Body Image Concern Among Healthcare Employees in Binaloud, Iran - Mozhgan Mahdifar; Seyedeh Belin Tavakoly sany; Vahid Ghavami; Mohammad Vahedian-Shahroodi (Mashhad University of Medical Sciences, 2021)
Background and Objective: Health literacy has been implicated as one of the main factors in improving public health maintenance, the present study examined the relationship between health literacy toward body image concern and respondents' demographic factors in healthcare employees in Binaloud, Iran. Materials and Methods: This cross-sectional survey was conducted on 170 healthcare employees in Binaloud, Iran. The full version of the self-administered Multidimensional Body-Self Relations Questionnaire (MBSRQ) and Health Literacy for Iranian Adults (HELIA) questionnaires were used as validated self-report measures to examine body image concerns and health literacy of participants. We used SPSS Statistics 16 (Chicago, Illinois) to conduct the descriptive statistics and preliminary analyses such as χ2, ANOVA, and Pearson correlation. Results: Results showed that 56.6% of participants had adequate health literacy, 24.4% had marginal, and 19% had inadequate health literacy. The mean score of the overall body image levels in the female and male participants were 256.45 ± 25.3 and 256.4 ± 21.6, respectively. There was a significant relationship (r=0.149; p <0.05) between health literacy and overall body image. Conclusion: This finding reflected a significant and positive relationship between overall body image score and the health literacy skills such as decision-making, understanding, and reading. We suggested a home/workplace intervention program to improve employees' body image concerns.